2016
DOI: 10.1681/asn.2016030374
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-Oxide and Cardiovascular Events in Hemodialysis Patients

Abstract: Cardiovascular disease causes over 50% of the deaths in dialysis patients, and the risk of death is higher in white than in black patients. The underlying mechanisms for these findings are unknown. We determined the association of the proatherogenic metabolite trimethylamine N-oxide (TMAO) with cardiovascular outcomes in hemodialysis patients and assessed whether this association differs by race. We measured TMAO in stored serum samples obtained 3-6 months after randomization from a total of 1232 white and bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
127
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 36 publications
8
127
1
Order By: Relevance
“…For instance, TMAO exhibited no significant predictive value on CVEs and mortality in a 4‐year observational cohort including 235 patients with CKD . Similar result was obtained from a more recent U.K. study in patients with HF . Two studies from Norway enrolling patients with CAD and HF also failed to show any evident correlation between TMAO and risk of death .…”
Section: Discussionsupporting
confidence: 66%
“…For instance, TMAO exhibited no significant predictive value on CVEs and mortality in a 4‐year observational cohort including 235 patients with CKD . Similar result was obtained from a more recent U.K. study in patients with HF . Two studies from Norway enrolling patients with CAD and HF also failed to show any evident correlation between TMAO and risk of death .…”
Section: Discussionsupporting
confidence: 66%
“…Details of trimethylamine-N-oxide (TMAO), asymmetric and symmetric dimethylarginines (ADMA and SDMA) measurements have been previously described. 19, 22 …”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, the small volume of distribution enables adequate clearance by dialysis. In HEMO study participants, higher TMAO concentrations were associated with a higher risk of sudden cardiac death, first cardiovascular event, and any-cause death, particularly in whites [46]. A cross-sectional study by Aki Mafune et al observed elevated TMAO levels in CKD patients who underwent cardiovascular surgery ( n = 227) [47].…”
Section: Tmao In Chronic Kidney Diseasementioning
confidence: 99%